Effect of Timing of Artificial Insemination on Fertility of Cows and Calf Sex Ratio in Arsi Cows - Arega, Alemayehu; Tesfaye Alemu Aredo; Girma Chalchissa (Discoveries in Agriculture and Food Sciences, 2023)
An on-station study was conducted to investigate the effect of the interval between artificial insemination (AI) and the beginning of estrus on the fertility and sex ratio of offspring in Arsi cows. Standing to be mounted was considered the beginning of estrus, and artificial inseminations were made 6 h (Group 1), 12 h (Group 2), 18 h (Group 3) and 24 h (Group 4) after the onset of estrus in the cows. Overall, 50 cows with parity between 2 and 4, body weight ranging from 250 to 300 kg were used for the purpose of this study. Ovulation was synchronized by administration of PGF2α hormone. Pregnancy diagnosis was performed by rectal palpation at 90 to 120 days post AI. Pregnancy rates were 60%, in each of the Groups 1, 2, 3 and 50% in group 4. The highest female to male ratio (P=0.041) of calves was obtained in Group 1. Whereas the highest male to female ratio was recorded in group 4. The number of artificial inseminations per pregnancy was within the economical limits in all groups. In conclusion, the results of this study indicated that the variation in time interval between the onset of estrus and artificial insemination alters the sex ratio of offspring in Arsi cows without affecting fertility parameters.